Fingerprint signatures based on nanomagnets as markers in materials for tracing and counterfeit protection - Szielasko, Klaus; Youssef, Amir; Sporn, Dieter; Mandel, Karl (Journal of Nanoparticle Research, 2016)
Abstract: Identification and tracing of objects is a challenge of great current importance. Ideally, this can be achieved via small markers, which equip an object with a fingerprint identity. Herein, we communicate an approach that is based on structural arrangements of magnetic nano-entities to generate a kind of security key in an object. The nano-markers, which are applied as inks, can remotely be read out in a fast and simple way with a GMR sensor and yield an unmistakable signal pattern. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2020-04-02
Keywords: Counterfeit protection; Fingerprint; GMR; Markers; Nanomagnets; Superparamagnetism